ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN NON ASN DAN PENGENDALIAN INTERNAL DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI PADA DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN SUKABUMI - Gunawan, Muhamad Sahrul; Suwiryo, Darmo H.; Tanjung, Hendra (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Payroll Accounting Information System and Internal Control are important aspects in managing a government agency because a good payroll accounting information system and internal control can provide accurate information and avoid errors in payroll so that it can improve employee performance. The type of research used is a qualitative descriptive method, the data processed is the result of unstructured interviews and observations that will be analyzed qualitatively and described in descriptive form. The results of the study show that the implementation of the Non ASN payroll accounting information system and internal control has been running well in improving employee performance. However, the Sukabumi Regency Trade and Industry Service needs to improve the attendance recording system which is still done manually as one of the weaknesses that needs to be improved into a computerized system to avoid fraud. In addition, internal control related to organizational structure also needs to be improved to separate the performance of employee tasks and functions more effectively and add human resources in several parts to prevent a decline in performance